Past, Present, and Future Perspectives of Plasminogen Activator Inhibitor 1 (PAI-1) - Morrow, Gael B.; Mutch, Nicola J. (Seminars in Thrombosis and Hemostasis, 2022)
Plasminogen activator inhibitor 1 (PAI-1), a SERPIN inhibitor, is primarily known for its regulation of fibrinolysis. However, it is now known that this inhibitor functions and contributes to many (patho)physiological processes including inflammation, wound healing, cell adhesion, and tumor progression.This review discusses the past, present, and future roles of PAI-1, with a particular focus on the discovery of this inhibitor in the 1970s and subsequent characterization in health and disease. Throughout the past few decades diverse functions of this serpin have unraveled and it is now considered an important player in many disease processes. PAI-1 is expressed by numerous cell types, including megakaryocytes and platelets, adipocytes, endothelial cells, hepatocytes, and smooth muscle cells. In the circulation PAI-1 exists in two pools, within plasma itself and in platelet α-granules. Platelet PAI-1 is secreted following activation with retention of the inhibitor on the activated platelet membrane. Furthermore, these anucleate cells contain PAI-1 messenger ribonucleic acid to allow de novo synthesis.Outside of the traditional role of PAI-1 in fibrinolysis, this serpin has also been identified to play important roles in metabolic syndrome, obesity, diabetes, and most recently, acute respiratory distress syndrome, including coronavirus disease 2019 disease. This review highlights the complexity of PAI-1 and the requirement to ascertain a better understanding on how this complex serpin functions in (patho)physiological processes.
Keywords: PAI-1; thrombosis; ARDS; obesity; metabolic syndrome